Preconception Maternal Iodine Status Is Positively Associated with IQ but Not with Measures of Executive Function in Childhood. Issue 6 (15th May 2018) - Robinson, Sian M; Crozier, Sarah R; Miles, Elizabeth A; Gale, Catharine R; Calder, Philip C; Cooper, Cyrus; Inskip, Hazel M; Godfrey, Keith M
Abstract: Background: Adverse effects of severe maternal iodine deficiency in pregnancy on fetal brain development are well-established, but the effects of milder deficiency are uncertain. Most studies examine iodine status in pregnancy; less is known about iodine nutrition before conception. Objective: We examined relations between maternal preconception iodine status and offspring cognitive function, within a prospective mother-offspring cohort. Methods: Maternal iodine status was assessed through the use of the ratio of iodine:creatinine concentrations (I/Cr) in spot urine samples [median (IQR) period before conception 3.3 y (2.2–4.7 y)]. Childhood cognitive function was assessed at age 6–7 y. Full-scale IQ was assessed via the Wechsler Abbreviated Scale of Intelligence, and executive function through the use of tests from the Cambridge Neuropsychological Test Automated Battery (CANTAB). Analyses ( n  = 654 mother-child dyads) were adjusted for potential confounders including maternal intelligence, education, and breastfeeding duration. Results: The median (IQR) urinary iodine concentration was 108.4 µg/L (62.2–167.8 µg/L) and the I/Cr ratio 114 µg/g (76–164 µg/g). The preconception I/Cr ratio was positively associated with child IQ, before and after adjustment for potential confounding influences [β = 0.13 (95% CI: 0.04, 0.21)/SD, P  = 0.003]. 8.9% of women had a preconception urinary I/Cr ratio <50 µg/g; compared with those with an I/Cr ratio ≥150 µg/g, the IQ of their offspring was 0.49 (95% CI: 0.79, 0.18) SD lower. There were no associations with the executive function outcomes assessed via CANTAB, before or after adjustment for confounders. Conclusion: The positive association between iodine status before conception and child IQ provides some support for demonstrated links between low maternal iodine status in pregnancy and poorer cognitive function reported in other studies. However, given the negative effects on school performance previously observed in children born to iodine-deficient mothers, the lack of associations with measures of executive function in the present study was unexpected. Further data are needed to establish the public health importance of low preconception iodine status.